直齿轮轮齿变形计算的数值积分法 - 颜海燕; 唐进元; 宋红光 (Jixie chuandong)
The numerical integral formula based on Weber energy method is deduced. Computing programs are written and the results are achieved compared with FEM, this numerical integial method is proved to be preciser and easy for programming.